Longitudinal Associations Between Indirect Peer Victimization, Friendship Quality, and Anxiety in Young Adulthood - Karasz, Sarah (Université d'Ottawa / University of Ottawa, 2026)
Friendships serve as vital sources of healthy social functioning in young adulthood, but these same relationships can also be a source of indirect peer victimization (IPV), involving covert forms of social maltreatment such as gossip and exclusion. In this thesis, I examined how IPV, poor friendship quality (PFQ), and anxiety influence one another over time. Using four annual waves from ages 22 to 26 (N= 443), a model building and cross-lagged panel approach was used to compare interpersonal-risk, symptoms-driven, and transactional models. Results indicated that the transactional model best fit the data. Indirect effects revealed support for interpersonal-risk driven pathways, such that IPV contributed to higher anxiety through deteriorating friendships, as well as greater IPV predicted subsequent heightened anxiety, which in turn predicted future victimization. Two additional, smaller indirect effects extended the sequence from IPV → PFQ → Anxiety to later IPV: PFQ predicted greater IPV through heightened anxiety, and IPV predicted later victimization through poorer friendship quality and heightened anxiety. Gender analyses showed some variation in auto-regressive and covariance paths, while multi-group comparisons revealed anxiety predicted poor friendship quality for men, and IPV showed stronger stability for women earlier in the study and for men at later time points, including over a two-lag span. Gender differences in indirect effects showed that the anxiety-mediated IPV loop was significant for women only. Results suggest that psychosocial distress in young adulthood is best conceptualized as a transactional system in which IPV, PFQ, and anxiety continually influence one another over time.
Keywords: Longitudinal; Indirect peer victimization; Friendship quality; Anxiety symptoms; Young adulthood; Gender differences